SONOGRAPHIC EVALUATION OF ADULT RENAL VOLUME AND ITS CORRELATION WITH BODY SURFACE AREA - Hafizhalaila Ammar; Evo Elidar Harahap; Alwi Thamrin Nasution; Henny Maisara Sipahutar; Elvita Rahmi Daulay; Netty Delvrita Lubis; Putri Chairani Eyanoer (PT. Radja Intercontinental Publishing, 2025)
Background: Renal size and volume play important roles in the diagnosis, treatment, and evaluation of renal pathology, and are excellent predictors of renal function. Renal size is associated with somatic growth parameters such as height, weight, and age, which are related to body mass index and body surface area. Objective: The aim of this study is to determine renal volume in the adult population using ultrasound and to analyze factors affecting the renal volume in patients. Methods: This was a case-series study of 35 renal in adult patients aged from >19 to 59 years without renal pathology. Renal length, width, depth, mean volume, and cortical thickness were sonographically measured. Patient age, gender, weight, height, and body surface area were recorded. Results: The mean body weight, body height, and body surface area were 69.8 ± 18.6 kg, 159.7 ± 8.1 cm, and 1.7 ± 0.2 m2, respectively. There was a significant difference in mean renal volume between the right and left renal, with measurements of 107 ± 30,9 cm3 and 125,5 ± 27,8 cm3, respectively. The mean renal volume in male was 118,4 ± 37,2 cm3 and 137,2 ± 32,6 cm3 for the right and left sides, respectively, and was found to be larger than in females. Both renals had a mean cortical thickness of 1.3 ± 0.1 cm. There was a positive and significant correlation between renal volume and body surface area (r=0.805 for the right renal, and r=0.604 for the left renal) with p<0.001. Conclusions: Renal volume is positively and significantly correlated with body surface area. Body index, age, gender, and side should also be taken into consideration when reporting renal volume.